RESULTS OF MONITORING OF MINERAL METABOLISM DISORDERS IN BOROUGH COWS - Makhsudov U.T.; Eshburiyev S. B.; Hamroqulov N. Sh (Web of Journals Publishing, 2025)
This article describes the causes, clinical, physiological, and hematological indicators of mineral metabolism disorders in 8-9-month-old Simmental cows in cattle farms, as well as an analysis of the condition of calves born from them.
Keywords: Cows, minerals, calcium, phosphorus, magnesium, potassium, hypodynamia, lizukha, bone dystrophy, alopecia, conjunctivitis, xerophthalmia.